SOLUBLE TRANSFERRIN RECEPTOR: A DIFFERENTIATING MARKER BETWEEN IRON DEFICIENCY ANAEMIA AND ANAEMIA OF CHRONIC DISORDERS - Saboor, Muhammad; Moinuddin, Moinuddin; Noreen, Ayesha (Journal of Ayub Medical College Abbottabad, 2011)
Background: Iron deficiency anaemia and anaemia of chronic disorders are the two major causes of microcytic and hypochromic anaemia. Many times the diagnosis of these conditions becomes difficult through conventional laboratory tests. Determination of soluble transferrin receptors is a helpful laboratory test for the differential diagnosis of these conditions. The study was conducted to evaluate the role of soluble transferrin receptors in the differential diagnosis between iron deficiency anaemia and anaemia of chronic disorders. Methods: A total of 80 blood samples were evaluated, i.e., 20 samples from normal adult male, 20 samples from normal adult female, 20 samples from iron deficiency anaemia group and 20 samples from patients with anaemia of chronic disorders. Soluble transferrin receptors were determined by ELISA technique using Quantikine IVD kit (R and D Systems). Results: There was significant difference in the levels of sTfR in iron deficiency anaemia and anaemia of chronic disorders. Statistically non-significant difference was observed between the levels of sTfR in patients with anaemia of chronic disorders as compared to normal control group. Conclusion: The sTfR determination can be used as a reliable differentiating marker in the diagnosis of iron deficiency anaemia and anaemia of chronic disorders. Keywords: sTfR, iron deficiency anaemia, anaemia of chronic disorders